Pengaruh Latihan Small Side Game Terhadap Akurasi Passing Futsal di Ekstrakurikuler SMPN 5 Cianjur : (Penelitian Free Eksperimen di Smpn 5 Cianjur) - Arief Adhitia Hamzah; Ai Faridah; Acep Ruswan; Dian Permana; Bela Santika; Muhamad Algifari Mu'minin (Lembaga Pengembangan Kinerja Dosen, 2024)
The focus of this research is the low passing accuracy skills of students in futsal games. The purpose of this study was to determine